The complexity of extracting knowledge in Big Data / Rozianiwati Yusof...[et al.] - Yusof, Rozianiwati; Manaf, Maznie; Mohd Zin, Nor Asma; Jamaludin, Marhainis (Unit Penerbitan UiTM Kelantan, 2016)
Big data is extremely large data set data in the range of exabytes and the volume of data cannot be processed efficiently with the traditional technology in term of storing, manage and process. With the technologies appear, big data has attracted many researchers to extract knowledge from it. The knowledge can be produced in making a decision. However, there are some issues existed in extracting the important knowledge such as in storing the data, managing the data and processing the data in extracting useful information since its relate with volume, velocity and variety. Therefore, this paper is attempting to list all the possible knowledge that can be extracted from big data as well as discuss the previous researches in knowledge extraction from the huge amount of data. The problem in extracting importantknowledge will be examined thoroughly and by identifying the significant problems in knowledge extraction the best knowledge from big data could be revealed. The techniques in analysing big data will be also discussed in the next section